Yorkie Negatively Regulates the Expression of Antimicrobial Proteins by Inducing Cactus Transcription in Prawns Macrobrachium nipponense - Huang, Ying; Si, Qin; Du, Jie; Ren, Qian (Frontiers in Immunology, 2022)
The Hippo signaling pathway controls organ size and immune system in Drosophila and mammals. Yorkie acts as a transcriptional co-activator in the Hippo pathway and cross-talks with other essential pathways. In this study, a Yorkie gene and two Cactus isoforms (designated as MnYorkie, MnCactus-a, and MnCactus-b, respectively) were isolated and characterized from oriental river prawns (Macrobrachium nipponense). Results showed that MnYorkie includes 1620 bp open reading frame and encodes a protein of 539 amino acids (aa). MnCactus-a (377 aa) and MnCactus-b (471 aa) were produced by alternative splicing. MnYorkie and MnCactus were continuously expressed in all selected tissues. Upon Gram-positive bacterium Staphylococcus aureus and Gram-negative bacterium Vibrio parahaemolyticus stimulation, the mRNA levels of MnYorkie and MnCactus in hemocytes and intestines underwent time-dependent enhancement. RNA interference studies showed that MnYorkie silencing remarkably downregulated the transcription of MnCactus but upregulated the expression of seven immune-related genes. In addition, MnYorkie silencing in vivo decreased the susceptibility of prawns to bacterial challenge. After S. aureus and V. parahaemolyticus infection, the survival rate of prawns increased significantly from 2 to 6 days, which corresponded to the period of MnYorkie knockdown. All these findings suggested that MnYorkie in the Hippo pathway might exhibit remarkable biological roles in the immune defense of M. nipponense by negatively regulating the expression of immune-related genes and promoting the transcription of MnCactus.